Abiotic Stresses Cause Differential Regulation of Alternative Splice Forms of GATA Transcription Factor in Rice - Gupta, Priyanka; Nutan, Kamlesh K.; Singla-Pareek, Sneh L.; Pareek, Ashwani (Frontiers in Plant Science, 2017)
The GATA gene family is one of the most conserved families of transcription factors, playing a significant role in different aspects of cellular processes, in organisms ranging from fungi to angiosperms. GATA transcription factors are DNA-binding proteins, having a class IV zinc-finger motif CX2CX17–20CX2C followed by a highly basic region and are known to bind a consensus sequence WGATAR. In plants, GATAs are known to be involved in light-dependent gene regulation and nitrate assimilation. However, a comprehensive analysis of these GATA gene members has not yet been highlighted in rice when subjected to environmental stresses. In this study, we present an overview of the GATA gene family in rice (OsGATA) in terms of, their chromosomal distribution, domain architecture, and phylogeny. Our study has revealed the presence of 28 genes, encoding 35 putative GATA transcription factors belonging to 7 subfamilies in the rice genome. Transcript abundance analysis in contrasting genotypes of rice - IR64 (salt sensitive) and Pokkali (salt tolerant), for individual GATA members indicated their differential expression in response to various abiotic stresses such as salinity, drought, and exogenous ABA. One of the members of subfamily VII - OsGATA23a, emerged as a multi-stress responsive transcription factor giving elevated expression levels in response to salinity and drought. ABA also induces expression of OsGATA23a by 35 and 55 folds in IR64 and Pokkali respectively. However, OsGATA23b, an alternative splice variant of OsGATA23 did not respond to above-mentioned stresses. Developmental regulation of the OsGATA genes based on a publicly available microarray database showed distinct expression patterns for most of the GATA members throughout different stages of rice development. Altogether, our results suggest inherent roles of diverse OsGATA factors in abiotic stress signaling and also throw some light on the tight regulation of the spliced variants of OsGATA genes in response to different environmental conditions.